(untitled) (Biological Sciences - PJSIR, 1998)
Earlier study on the measurement of level of noise emitted from freely flowing individual motorcycles, buses and rick- shaws has been extended and noise emission data for cars, trucks and motor vehicle horns collected to assess their contribution to road traffic noise in Karachi city. The data collected has been analyzed for Lwo’ Ly Oand LylOand the results are discussed with reference to maximum permissible noise emission limits for motor vehicles as allowed by Pakistani and other national standards.